“ ISUZI ” TRUCKS IN HIGH MOUNTAIN AND HOT CLIMATES (Multidisciplinary Journal of Science and Technology, 2026)
this article presents scientific research on the “ ISUZI ” truck operating in the highlands and hot climate of the Republic of Uzbekistan. The operation of the “ ISUZI ” car in hot climates, transport operating conditions, road operating conditions, natural and climatic operating conditions have been studied, and the main factors influencing changes in the quality of engine oil during engine operation have been analyzed.